STRATEGY OF THE DEPARTMENT OF COMMUNICATION, INFORMATICS, CODE AND STATISTICS IN PUBLIC INFORMATION SERVICES IN KAPUAS REGENCY - Fika Fibriyanita; Normajatun; Utari Nur Fitriani (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The purpose of this study was to determine the description of the strategy of the Communication, Informatics, Coding and Statistics Office of Kapuas Regency in public information services and the obstacles in providing public information services through the kip.kapuaskab.go.id website portal. The research method uses a qualitative approach with descriptive research. Data were collected by observation, documentation, and interviews with 4 informants. Data analysis using qualitative data analysis. The results showed strategy implemented by the Communication, Informatics, Coding and Statistics Office of Kapuas Regency in public information services through the kip.kapuaskab.go.id website, namely: 1) core strategy, by determining the organizational structure, work system and employee placement based on education, 2) consequence strategy, implemented with giving appreciation, support and reprimand to employees to maintain performance, 3) customer strategy, implemented with standard operating procedures for services and complaints, 4) control strategy, by conducting evaluations through community satisfaction surveys and 5) cultural strategy, habits of mutual cooperation and cooperation by employees in carrying out services. The obstacles to public information services through the website are internet network access and server maintenance down.